Efecto del arreglo espacial de plantas sobre el rendimiento del maiz en la región Huetar atlántica de Costa Rica (ING) - Munguía Ulloa, Sayra (Uniciencia, 1995)
A trial was carried out in the Huetar Atlantica region with different spatial arrays of plants and the same plant density (6 plants m-2), in order to determine the existence of an effect of the sowing structure in the final yield of corn. The results show a negative effect as the space asymmetry increased as a consecuence of the increment of the space between plants and the number of seeds per hole. This produces an interplant competition for solar radiation and nutrients. Taking into account the results, it is convenient to use a spatial arrangement that allows a more regular plant distribution. When sowing is made manually, it would be recommendable to use 2 or 3 seeds per hole to improve the yield of the region producers.